Assessment of The Quality of Borehole Water in Kanenankumba Village Hoima Municipality. - Tayeebwa, Joshua (Kabale University, 2024)
The purpose of the study was to assess the quality of borehole water in Kanenankumba village, Hoima municipality. The objectives employed were; to determine the physical and micro-biological water quality parameters, compare the obtained physical and micro-biological parameters with standard values outlined by WHO and also determine the local methods that can be employed to purify borehole water. The findings indicated that all the physical parameters met the standard requirements set for drinking water by WHO and the microorganisms (fecal coliforms) found present were enough to tell the level of contamination of the water. To eliminate the fecal coliforms in the water sample to a number acceptable by WHO in its guidelines, methods like boiling to 100" C and the use of household bleach were practically proven to be most effective during the study.